PERANCANGAN SISTEM KOMUNIKASI VOIP (Voice Over Internet Protocol) BERBASIS SIP DENGAN MENGGUNAKAN METODE PPDIOO PADA PT. APLIKANUSA LINTASARTA MEDAN - Johannes Badia Raja Simanungkalit (Jurnal Sains dan Teknologi, 2019)
The results of research at PT. Aplikanusa Lintasarta Medan, was found to be a problem in thecommunication system that is inefficient and not yet mobile. As well as the high cost of maintenance (maintenance)devices on the communication system currently in use. For this reason VoIP exists as a solution to the problem ofcommunication systems that are cost-efficient and efficient. In designing VoIP, the method used is the PPDIOO method(Prepare, Plan, Design, Implement, Operate, Optimize). This method is used to design in the initial stages, until therefinement stage. The implementation phase uses the 3CX Phone System application which functions as a server, andX-Lite / Zoiper as a softphone. The voice produced by VoIP is clear, there is no noise, and there is no pause whenmaking phone calls between users